Efficacy of Post-Extraction Suturing on the Incidence of Dry Socket Occurrence in Erupted and Semi-Erupted Mandibular Third Molar: A Case-Control Study - Saeed, Aram Sabr; Amin, Zanyar Mustafa (Sulaimani Journal for Pure and Applied Sciences, 2022)
Objectives: The main aim of this study is to evaluate the incidence of dry sockets in patients in relation to their clinical parameters such as pain, the disintegration of the clot, and halitosis regardless of their oral hygiene status. Also, to find sex and age-related to the reported parameters during surgical technique (time and complication). Methods: A prospective cross-sectional study was done on 60 patients (30 study group and 30 control group) aged 21 -50 years with semi-erupted and full-erupted lower 3rd molars, which were indicated for extraction. The mandibular 3rd molar was extracted without any suturing in the control group, while extraction of the 3rd molar for the study group using a figure-eight suture. All the patients were evaluated for pain, presence of clot and condition of the alveolar bone to diagnose dry socket. Results: The incidence of dry sockets was only 3 cases (5%) (one in study group and another two in control group) who were male heavy smokers. Regarding the clinical signs after 3, 5, and 7 days of tooth extraction, pain was severe/very severe in 3.3% at extraction sites in the study group and 6.7% in the control group on the 3rd day. While, the pain was moderate in 3.3% and 6.7% at extraction sites in the study and control groups, respectively, on the 5th day. In both groups, the blood clot was found in 100% of extraction sites on the 5th and 7th days but it was not found in 3.3% and 6.7% of extraction sites in study and control groups on the 3rd postoperative day, respectively. Also, halitosis was found in only 1% of the control group on the 3rd day but it was absent in 100% of the study group on the 3rd, 5th, and 7th postoperative days and the control group on the 5th and 7th days. Conclusions: We realized that the incidence of dry sockets was less without significant difference in patients with a figure-eight suturing of extraction site that might be the cause for reducing pain in a study group as well as the amount of blood clot on 3rd postoperative day.
Keywords: Figure-eight suture; Semi-erupted mandibular third molar; Alveolar osteitis; cross-sectional study